2020
DOI: 10.2478/aoas-2020-0011
|View full text |Cite
|
Sign up to set email alerts
|

Skin Mucosal, Serum Immunity and Antioxidant Capacity of Common Carp (Cyprinus carpio) Fed Artemisia (Artemisia annua)

Abstract: In this study, the effect of artemisia (Artemisia annua) leaves extract (ALE) on the immune system, growth performance and antioxidant capacity of common carp (Cyprinus carpio) was investigated. Fish with initial weight (90.32 ± 1.12 g) were fed various levels of ALE (0, 0.5, 1 and 1.5 g/kg) for 8 weeks. The results showed that the growth performance (FW, WG, SGR, PER, and LER) in fish fed 1 g/kg ALE was increased significantly (P<0.05) and the feed conversion ratio (FCR) was improved in fish fed 1 and 1.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 84 publications
6
27
1
Order By: Relevance
“…However, the rate of 4% displayed reduced growth performance when compared to the other groups. In concurrent with the present study, several medicinal herbs resulted in improving the growth rate, probably due to the increased palatability which associated with increased feed intake (Sarhadi et al, 2020;Srichaiyo et al, 2020). However, the high supplementation levels decreased the growth performance, which can be attributed to the high contents of polyphenols and fibers (Ji et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…However, the rate of 4% displayed reduced growth performance when compared to the other groups. In concurrent with the present study, several medicinal herbs resulted in improving the growth rate, probably due to the increased palatability which associated with increased feed intake (Sarhadi et al, 2020;Srichaiyo et al, 2020). However, the high supplementation levels decreased the growth performance, which can be attributed to the high contents of polyphenols and fibers (Ji et al, 2018).…”
Section: Discussionsupporting
confidence: 77%
“…It can be assumed that SP supplementation resulted in an induced antioxidative response either by the improvement of the action of the SOD and CAT enzymes or by removing the extra ROS produced and accordingly avoiding lipid peroxidation (MDA increase) due to its content of phycocyanin and carotenoids [33]. SP has a high content of β-carotene which can scavenge ROS molecules including "peroxyl, alkoxyl, and hydroxyl radicals" besides its role in the reduction of nitrite and nitric oxide synthase to minimize the liver lipid peroxidation [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, fish fed with the 200 ml/kg of LEON had the highest SOD level and other immunity parameters. Previous study showed that the oral administration of rosemary leaf powder (Yousefi et al 2019) and artemisia (Artemisia annua) extract (Sarhadi et al 2020) improved SOD activity in common carp. In addition, Rafieepour et al (2018) showed that different concentrations of oregano extract (Origanum vulgare L.) significantly increased serum SOD activity in rainbow trout.…”
Section: Discussionmentioning
confidence: 99%